Effects of Coping Style Training on the Treatment Adherence in Adolescents with Congenital Heart Disease - L Shirkavand; F Alaee Karahroudy; J Mohtashami; E Ghasemi (Iran University of Medical Sciences, 2019)
on coping styles on the treatment adherence of adolescent patients with congenital heart disease.  Materials & Methods: This experimental study was conducted with a pretest-posttest design and a control group on 70 adolescents aged 9-19 years with congenital heart disease at Shahid Rajaee Heart Center in Tehran, Iran in 2018. The patients were selected via continuous sampling and divided into two groups of intervention and control via simple random sampling. In addition to routine care, the subjects in the intervention group received training based on stress coping styles in the form of educational contents. Data were collected using Folkman and Lazarus ways of coping questionnaire, and the control group received routine care within the department. Data analysis was performed in SPSS version 16 using independent and paired t-test, Chi-square, and Fisher's exact test. Results: Independent t-test indicated a significant difference in the mean score of treatment adherence between the groups, and the score was observed to be higher in the intervention group (P=0.002). In addition, the mean score of treatment adherence had a significant difference in the intervention group before and after the training (P>0.001). Conclusion: Considering the positive effect of training based on stress coping styles on the treatment adherence of adolescents with congenital heart disease, it is recommended that healthcare providers incorporate these styles into the treatment protocol of these patients in the form of consultation and educational courses